2019
DOI: 10.1177/1948550619829067
|View full text |Cite
|
Sign up to set email alerts
|

Lest We Forget: The Effect of War Commemorations on Regret, Positive Moral Emotions, and Support for War

Abstract: Why do societies commemorate war? The persistence of war commemorations suggests they serve a purpose in society. We examine one possibility: Commemorating past sacrifices may serve an “inspirational” function, by evoking pride and gratitude for soldiers’ actions and promoting a willingness to endure future sacrifices for the group. We contrast this with the (popularly espoused) “preventative” function, whereby commemorations decrease support for war by evoking regret. Drawing on one correlational study ( N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 18 publications
7
10
0
Order By: Relevance
“…Our studies directly build on and are largely consistent with some previous research on the effect of (collective) memories of war on militarism and diplomacy: In all samples except France we found that participants expressed more positive moral emotions (e.g., pride, gratitude) on commemorative days than at baseline, consistent with Watkins and Bastian (2019; see also Jonas et al, 2008Jonas et al, , 2013. However, our findings are inconsistent with other research on collective memories -reviewed in the introduction -which suggests that commemorations might increase militarism and intergroup conflict (e.g., Chatard et al, 2011;Li et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our studies directly build on and are largely consistent with some previous research on the effect of (collective) memories of war on militarism and diplomacy: In all samples except France we found that participants expressed more positive moral emotions (e.g., pride, gratitude) on commemorative days than at baseline, consistent with Watkins and Bastian (2019; see also Jonas et al, 2008Jonas et al, , 2013. However, our findings are inconsistent with other research on collective memories -reviewed in the introduction -which suggests that commemorations might increase militarism and intergroup conflict (e.g., Chatard et al, 2011;Li et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Results of these analyses are presented in Table 2, along with descriptive statistics. Participants reported greater positive moral emotions on Veterans Day than at baseline, consistent with Watkins and Bastian (2019). Consistent with this finding, we also found that negative emotions were lower on Veterans Day compared to baseline.…”
Section: Nine Participants Who Responded Incorrectly To the Attentionsupporting
confidence: 87%
See 3 more Smart Citations